Depersonalization and escaping to nature: a comfort woman’s journey in Therese Park’s A Gift of the Emperor - Somia, Ayaicha; Mani, Manimangai; Jujar Singh, Hardev Kaur; Awang, Mohamed Ewan (2018)
The Japanese occupation during the WWII transcended beyond conquering countries to conquering bodies through the adaptation of sexual slavery in the Asian colonized countries, especially China and Korea. The Japanese colonization aimed at distorting the colonized subjects’ identities specifically the Korean comfort women who were the most drafted sexual slaves. These radical changes lead to the traumatization of the enslaved girls whose reactions varied and they fostered different ways to deal with their trauma. The latter is vividly depicted in the selected literary work for this research. Therese Park’s A Gift of the Emperor (1997) tells the story of a 17 years old Korean schoolgirl who is used as a comfort woman along with her classmates. Her struggle to survive the traumatizing atmosphere of the military brothels is marked by her escape to the surrounding nature that she can see or hear to depersonalize herself while being brutally raped and tortured. The main character reflects the distressing physical and psychological effects of the war which is going to be the core of this study. Therefore, this research aims at identifying the effect of depersonalizing oneself and escaping to nature to deal with the trauma of sexual slavery. Through the lenses of psychology and ecopsychology, the protagonist’s coping mechanism will be analyzed to clarify the crucial role that nature can play in overcoming a psychological pain.